Gênero e sexualidade nos cursos de Pedagogia: um estudo sobre a Resolução CNE 002/2015 na formação inicial de professoras do Sudeste - Fabricio, Mariana Gonçalves (2020)
This dissertation aims to analyze the way in which the Pedagogy courses of federal universities in the Southeastern region of the country were reformulated to comply with Resolution No. 002/2015 of the National Education Council (CNE). Resolution No. 002/2015 makes it mandatory to contemplate gender discussions in teacher education along the pedagogical political projects of undergraduate courses in Pedagogy. As consequence of a problematization of the emergency conditions of this policy national public, which regulates the training of teachers, inferring about its consequences in pedagogy courses, which train teachers for small children. This research, of genealogical inspiration, is based on a documentary analysis of the pedagogical projects of the Pedagogy courses in the Southeastern region after the adequacy date foreseen by the resolution. The search for keywords in the documents, it was possible to observe the various exits found by the courses to adapt to the new requirements.